Carnage and care on the eastern front : the war diaries of Bernhard Bardach, 1914-1918 - Bardach, Bernhard, 1866-1947 (Berghahn Books, 2018)
For nearly all of the Great War, the Jewish doctor Bernhard Bardach served with the Austro-Hungarian army in present-day Ukraine. His diaries from that period, unpublished and largely overlooked until now, represent a distinctive and powerful record of daily life on the Eastern Front. In addition to key events such as the 1916 Brusilov Offensive, Bardach also gives memorable descriptions of military personalities, refugees, food shortages, and the uncertainty and boredom that inescapably attended life on the front. Ranging from the critical first weeks of fighting to the ultimate collapse of the Austrian army, these meticulously written diaries comprise an invaluable eyewitness account of the Great War.